(untitled) (Annals of Medical Research, 2021)
Aim: Initial treatment of secondary hyperparathyroidism (sHPT), often seen as a result of end-stage renal failure, is medical treatment. Treatment-resistant patients require surgery. The aim of this study is to evaluate the diagnosis and treatment of patients who underwent sHPT.Material and Methods: Twenty-one patients who were operated for sHPT were included in the study. The demographic data of the patients and correlation of imaging results with correct localization and pathological diagnosis were evaluated.Results: The mean age of the patients was 45.80±1.10. While the number of patients with growth in a parathyroid gland was 7 (32%), the number of patients with multiple glands was 8 (39%). According to scintigraphy evaluation, the same values were 4 (19%) and 12 (57%) patients. 7 (34%) patients were underwent adenoma excision, 11 (52%) patients were underwent subtotal parathyroidectomy and 3 (14%) patients were underwent total parathyroidectomy + parathyroid auto-implantation. Persistent hyperparathyroidism was seen in 2 patients who underwent subtotal parathyroidectomy and 1 patient who underwent adenoma excision. Conclusion: Today, the treatment of sHPT is still the best treatment option, and as a treatment, subtotal parathyroidectomy and total parathyroidectomy + parathyroid autoimplantation surgery should be preferred.